INDONESIAN HIGH SCHOOLERS’ PERCEPTIONS OF RUANGGURU IN ENGLISH ONLINE LEARNING - Fadhil Ramadhani; Ika Lestari Damayanti (JURNAL PENDIDIKAN GLASSER, 2023)
English language instruction in Indonesia has been impacted by the shift to online learning. One of the popular online learning platforms in the country is Ruangguru. Students can access its English learning resources anytime and anyplace. The purpose of this study is to investigate how Indonesian high school students view Ruangguru as an online resource for studying English. Data from the students who utilize Ruangguru was gathered via a questionnaire and facilitatied interviews. A mixed-methods approach was used to analyze the data, combining qualitative analysis with descriptive statistics. The findings show that Ruangguru is well-liked by online English learners, particularly because its videos provide straightforward instructions that can inspire the students to become independent learners. However, some students continue to have issues with the limitations imposed by online learning and digital gap. Regardless, the majority of students consider Ruangguru to be a valuable English learning source in the age of online education